Принципи організації інтер’єру в українській сакральній архітектурі першої чверті ХХ століття (на прикладі творчості Модеста Сосенка) - Радомська, Віолетта Радіонівна (Національний університет "Львівська політехніка", 2021)
В дисертації визначено основні принципи просторової організації монументальних стінописів і предметно-просторового наповнення інтер’єрів українських церков першої чверті ХХ ст. на прикладі проектно-художньої діяльності Модеста Сосенка (1875–1910). Систематизовано та узагальнено матеріали дотеперішніх досліджень, виконано натурні дослідження та ідентифіковано сакральні поліхромії М. Сосенка. Розкрито особливості застосування функціонального, композиційного, образно-семантичного, техніко-технологічного принципів, які характеризують творчий метод автора в дизайні сакральних інтер’єрів. Комплексні натурні дослідження, дозволили визначити існуючий стан збереженості монументальних творів, виявити етапи та причини руйнування та розробити і апробувати на практиці шляхи їх збереження. Визначено значення сакральної творчості М. Сосенка та сформульовано рекомендації щодо застосування цих принципів у сучасній проектно-художній дизайнерській діяльності. В диссертации определены основные принципы пространственной организации монументальных стенописей и предметно-пространственного наполнения интерьеров украинских церквей первой четверти ХХ века на примере проектно-художественной деятельности Модеста Сосенко (1875–1920). Систематизированы и обобщены материалы прежних исследований, выполнены натурные исследования и идентифицировано сакральные полихромии М.Сосенко. Раскрыты особенности применения функционального, композиционного, технико-технологического принципов, которые характеризируют творческий метод автора в дизайне сакральных интерьеров. Комплексные натурные исследования позволили определить текущее состояние сохранности монументальных произведений, разработать и апробировать на практике пути их сохранения. Определено значение сакрального творчества М.Сосенко и сформулированы рекомендации по применению этих принципов в современной проектнохудоженственной деятельности. The dissertation is dedicated to defining the principles of interior organization by means of murals in sacred architecture of the first quarter of the XX century. The results of the previous research studies have been systematized and generalized. The field observations aimed at locating and identifying the sacred polychrome paintings by the proclaimed monumentalist Modest Sosenko (1875–1910) have been conducted. The peculiarities of functional, compositional, figurative and semantic, technical and technological principles, which formed the basic scheme for characterizing the creative method of murals followed by the author while designing sacred interiors, have been outlined on the basis of the methodological graph analytics. The introduction justifies the relevance of the topic, determines the research aim and objectives, emphasizes the main scientific results of the research, and explains the topic value and practical application. The first chapter «Current state of the topic coverage of interiors in Ukrainian sacred architecture of the first quarter of the XX century» generalizes and systematizes the previous scientific studies of the object-spatial organization of sacred interiors, particularly the sources related to murals by Modest Sosenko (1875–1920), the monumentalist from Halychyna region. The topic of research is aimed at studying the constituent components that create modern interdisciplinary approaches connected with the design of the objectspatial environment. The methodological mechanisms, methods, and approaches to reaching the established objectives have been outlined and the stages of acquiring results and accomplishing the research objectives have been presented. The second chapter «Peculiarities of interior design development in Ukrainian sacred architecture of the first quarter of the XX century» provides the retrospective analysis of the establishment and development of sacred buildings construction in Halychyna region in the early XX century. The geopolitical and socio-cultural factors, which influenced the outburst of artistic life and, consequently, resulted in the active construction of sacred buildings and decoration of interiors, have been distinguished. The origins and tendencies of establishing functional and aesthetic peculiarities of the objectspatial environment of interiors in Ukrainian sacred architecture of the first quarter of the XX century have been specified. It has been determined that on the cusp of the XIX and XX centuries with the growth of economic development and national consciousness of Ukrainians residing in Halychyna region the brand-new necessity (or the so-called “social demand”) for creating new types of sacred buildings aimed at moving traditions onto the timely relevant, figurative, stylistic, and ideological level has appeared. In this context, the activity of the design and architectural company of Ivan Levynskyi in Lviv and the role of the sacred creativity of the monumentalist from Halychyna region Modest Sosenko (1875– 1920) have been highlighted. The third chapter «Creative method of Modest Sosenko in the interior design organization of Ukrainian church» focuses on the system of principles in accordance with which the creative method combining peculiar means and techniques has been established. As based on the graph analytics and the morphological analysis of murals structure, we have outlined the peculiarities of functional, compositional, figurative and semantic, technical and technological principles which formed the basic scheme for characterizing the creative method of the author in the design of sacred objects. The methodology of forming figurative, aesthetic, and semantic principles that ensure the possibility of perceiving wall polychrome paintings as the instrument of the object-spatial organization of sacred environment has been developed, enhanced, and generalized. The sources of inspiration of Modest Sosenko, which changed the representation and the established approach to figurative and theological perception of the new temple of the early XX century, have been specified. The fourth chapter «Preservation of the authenticity of historical sacred interiors in the context of modern design development» highlights the results of the comprehensive scientific and restoration research of the polychrome paintings by Modest Sosenko, which gave the opportunity to evaluate the current state of the monumental works, detect the stages and the reasons of destruction, and develop and implement the techniques of their preservation in practice. The suggested specialized methodology of research is recommended for the preservation of the authenticity of historical interiors within the course of modern monument protection activities in Ukraine. Particular attention is paid to the ways of integrating the methods, techniques, and principles of polychrome paintings by Modest Sosenko into the artistic and figurative organization of sacred space and their subsequent application in modern project and artistic design activity.
Принципы организации интерьера в украинской сакральной архитектуре первой четверти ХХ века (на примере творчества Модеста Сосенко)
Principles of interior organization in Ukrainian sacred architecture of the first quarter of the XX century (as based on the example of creative works by Modest Sosenko)
Keywords: стінопис; предметно-просторове середовище; принципи; організація інтер’єру; Модест Сосенко; сакральна архітектура; стенопись; предметно-пространственная среда; принципы; организация интерьера; Модест Сосенко; сакральная архитектура; mural; object-spatial environment; principles; interior organization; Modest Sosenko; sacred architecture; 72.04:726:72.012.8